Desempenho de cultivares e potencial fisiológico das sementes de milho produzidas em sistema orgânico - Martin, Bruna Cavinatti (2017)
Maize is one of the most cultivated cereals in the world and it is among the most important cereals for the consolidation of the production chains of meat, eggs, milk and derivatives in organic system, being one of the main components of the rations. However, there is still little information about the performance of cultivars and quality of maize seed produced in the organic this system. The present work aimed evaluate the performance of maize cultivars in the organic system, as well as the physiological potential of the seeds produced. The experiments were conducted between December 2015 and October 2016. The first experiment was accomplished in the 2015/2016 harvest in an experimental area conducted in the organic system for eight years, located at the Federal University of São Carlos, UFSCar, Agrarian Sciences Center, CCA, in Araras county, SP.Therefore, this study seek to rate the performance of commercial cultivars (improved and hybrid varieties) and local corn varieties in organic system, as well as to analyze the physiological quality of the produced seeds.The experiment was conducted in 2015/2016 crop, conducted in a eight-year organic system experimental area, placed in Universidade Federal de São Carlos (UFSCar), Centro de Ciências Agrárias (CCA), in Araras county, São Paulo. The experimental design used was a randomized blocks with seven treatments and four replications. Were tested three commercial varieties of corn: (AL Avaré, AL Bandeirantes and AL Piratininga), two hybrids (P30F53 AND 2B587) and two open pollinated variety - OPV (Santa Rita 1 and Santa Rita 2). The evaluated agronomic characteristics were: plant average height (PH), stem average diameter (SD), plants stand final(FS), average number of row per spike (NRS) average number of grains row (RGN) and average number of spike grains (SGN) average number, weight of 1000 grains (M1000), Falker chlorophyll index (FCI) and grain productivity (PROD).Also evaluted the leaf content nutrients N, P, K, Ca, Mg and S in cornmaize, the infestation rate (IR) e diseases severity of the spikes (DS) and the armyworm(Spodoptera frugiperda J.E. Smith) susceptibility. The results were submitted to analysis of variance and the means grouped by the Scott Knott test at a 5% level of significance. The second experiment was conducted at the Laboratory of Plant Production and Forest Resources of the CCA, UFSCar in the municipality of Araras-SP. The experimental design was a completely randomized, 7 x 2 factorial design with four replications. The first factor was the seeds of the maize cultivars and the second was the storage time of the seeds in PET bottles (zero and 90 days). For evaluete the physiological potential of the seeds were evaluated: weight of 1000 seed mass, first germination count, germination test, first germination count after, accelerated aging test and the emergency speed index. The results were submitted to analysis of variance and the averages were grouped by the Tukey statistical test, at the 5% level of significance. The hybrid 2B587 presents the best performance in organic farming, fact that is probably related to their drought tolerance, foliar nitrogen content and Falker chlorophyll index. It's important evaluate their perfomance in another crop because the perfomance should be the intrinsic characteristics of each grow crops and their environmental interaction. The seeds produced in organic system presented high vigor and percentage of germination, even after the storage in PET bottle, which maintained the quality after 90 days of storage.